Peptide-Based Nanoparticle for Tumor Therapy - Phonpilas Thongpon; Menghuan Tang; Zhaoqing Cong (Biomedicines)
Cancer treatment continues to face significant challenges due to the limitations of conventional therapies, including non-specific toxicity, poor bioavailability, and drug resistance. Nanotechnology, particularly peptide-based nanoparticles (NPs), is increasingly recognized as a valuable strategy to address these obstacles. Peptides provide a versatile platform offering high biocompatibility, specificity, biodegradability, and minimal immunogenicity, making them ideal for targeted cancer therapies. This review comprehensively examines recent advancements in peptide-based nanoparticle systems, highlighting the mechanisms driving peptide self-assembly, such as amphiphilicity, non-covalent interactions, and metal coordination. It distinguishes between non-bioactive peptide nanoparticles, which primarily serve as drug carriers, and bioactive peptide nanoparticles, which integrate targeting peptides, cell-penetrating peptides (CPPs), and therapeutic peptides to enhance specificity, internalization, and anticancer efficacy. Emphasis is placed on innovative designs that exploit active targeting, stimuli-responsive release, and immunomodulatory strategies to maximize therapeutic outcomes while minimizing side effects. Despite promising preclinical outcomes, the clinical translation of peptide nanoparticles struggles with challenges involving stability, delivery efficiency, scalability, regulatory compliance, and manufacturing complexity. The review concludes by outlining future directions, emphasizing personalized nanomedicine, combination therapies, and advanced peptide engineering as crucial pathways toward successful clinical implementation.